Achieving impact in research - Denicolo, Pam (Los Angeles : SAGE, 2014)
This exciting text helps researchers to successfully understand and achieve impact in their research, and to demonstrate this impact in order to secure funding and to show excellence in REF.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Research -- Methodology